A Nonribosomal Peptide Synthase Containing a Stand-Alone Condensation Domain Is Essential for Phytotoxin Zeamine Biosynthesis - Yingying Cheng; Xiaoling Liu; Shuwen An; Changqing Chang; Yuanqiang Zou; Luhao Huang; Jin Zhong; Qiongguang Liu; Zide Jiang; Jianuan Zhou; Lian-Hui Zhang (Molecular Plant-Microbe Interactions, 2013)
Dickeya zeae is the causal agent of rice foot rot and maize stalk rot diseases, which could cause severe economic losses. The pathogen is known to produce two phytotoxins known as zeamine and zeamine II which are also potent antibiotics against both gram-positive and gram-negative bacteria pathogens. Zeamine II is a long-chain aminated polyketide and zeamine shares the same polyketide structure as zeamine II, with an extra valine derivative moiety conjugated to the primary amino group of zeamine II. In this study, we have identified a gene designated as zmsK encoding a putative nonribosomal peptide synthase (NRPS) by screening of the transposon mutants defective in zeamine production. Different from most known NRPS enzymes, which are commonly multidomain proteins, ZmsK contains only a condensation domain. High-performance liquid chromatography and mass spectrometry analyses showed that the ZmsK deletion mutant produced only zeamine II but not zeamine, suggesting that ZmsK catalyzes the amide bond formation by using zeamine II as a substrate to generate zeamine. We also present evidence that a partially conserved catalytic motif within the condensation domain is critical for zeamine production. Furthermore, we show that deletion of zmsK substantially decreased the total antimicrobial activity and virulence of D. zeae. Our findings provide a new insight into the biosynthesis pathway of zeamines and the virulence mechanisms of the bacterial pathogen D. zeae.